2018
DOI: 10.5194/esd-9-865-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of the Northern Hemisphere snow cover response to 1.5 and 2.0 °C warming

Abstract: Abstract. The 2015 Paris Agreement set a goal to pursue a global mean temperature below 1.5 °C and well below 2 °C above preindustrial levels. Although it is an important surface hydrology variable, the response of snow under different warming levels has not been well investigated. This study provides a comprehensive assessment of the snow cover fraction (SCF) and snow area extent (SAE), as well as the associated land surface air temperature (LSAT) over the Northern Hemisphere (NH) based on the Community Earth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…To our knowledge, the isolated CC versus LUC effects on future land surface albedo have previously not been analyzed simultaneously, but even the literature on CC-induced changes in future snow cover and albedo is surprisingly scarce. CMIP5 models simulate Northern Hemisphere snow area reductions between 1971-2000 and 2071-2100 of~−5.6 ± 3.2% and −9.7 ± 3.5% in winter and −16.6 ± 13.8% and −25.1 ± 15.5% in summer for RCP2.6 and RCP4.5, respectively (A. H. Wang et al, 2018). This compares to satellite-based…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the isolated CC versus LUC effects on future land surface albedo have previously not been analyzed simultaneously, but even the literature on CC-induced changes in future snow cover and albedo is surprisingly scarce. CMIP5 models simulate Northern Hemisphere snow area reductions between 1971-2000 and 2071-2100 of~−5.6 ± 3.2% and −9.7 ± 3.5% in winter and −16.6 ± 13.8% and −25.1 ± 15.5% in summer for RCP2.6 and RCP4.5, respectively (A. H. Wang et al, 2018). This compares to satellite-based…”
Section: Discussionmentioning
confidence: 99%
“…CMIP5 models simulate Northern Hemisphere snow area reductions between 1971-2000 and 2071-2100 of~−5.6 ± 3.2% and −9.7 ± 3.5% in winter and −16.6 ± 13.8% and −25.1 ± 15.5% in summer for RCP2.6 and RCP4.5, respectively (A. H. Wang et al, 2018). CMIP5 models simulate Northern Hemisphere snow area reductions between 1971-2000 and 2071-2100 of~−5.6 ± 3.2% and −9.7 ± 3.5% in winter and −16.6 ± 13.8% and −25.1 ± 15.5% in summer for RCP2.6 and RCP4.5, respectively (A. H. Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researches had been conducted to understand the potential climate impacts of warming both below and above these threshold levels Wang et al, 2018;Zhang et al, 2018). Numerous researches had been conducted to understand the potential climate impacts of warming both below and above these threshold levels Wang et al, 2018;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches had been conducted to understand the potential climate impacts of warming both below and above these threshold levels Wang et al, 2018;Zhang et al, 2018). Wang et al (2018) found that the projected reduction in snow area extent under 1.5°C of warming is lower than that under 2°C of warming during the second half of the 21st century. Wang et al (2018) found that the projected reduction in snow area extent under 1.5°C of warming is lower than that under 2°C of warming during the second half of the 21st century.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation